La progettazione di nuovi spazi educativi per l’infanzia: da Ellen Key a Maria Montessori - Pironi, Tiziana (Studi sulla Formazione/Open Journal of Education, 2011)
The essay presents a comparison between the thought of Ellen Key and that of Maria Montessori. Changes that involved the role of women, caught in its interdependence with the development of new educational practices, were the center of the theoretical contribution of Ellen Key. Maria Montessori believed that only women work outside the home would guarantee the economic independence necessary to form a union on sentiment rather than on utilitarian calculations and therefore she did not seem to share the concerns of the Key on an increasingly massive female entry into the world of work. The paper offers an updated reflection on the work of two scholars of education.